Performing the Body in Irish Theatre - Sweeney, B. author. aut Link
XI, 241 p.
Keywords: This title examines the representation of the body in Irish theatre alongside the specific circumstances within which Irish theatre is performed, incorporating issues of gender and embodiment, and the performance of Irishness and tradition. The author contextualizes the body in Irish theatre, and includes in-depth analysis of five key productions.